Pengaruh akuntabilitas pajak terhadap efektivitas administrasi pajak: Bukti dari negara-negara bagian barat daya, Nigeria - Tajudeen Adejare Adegbite; Saliu Omotayo Ayinla; Adekunle Lukmon Lawal (Universitas Kristen Maranatha, 2026)
Tax accountability is a crucial element in modern government administration, fostering transparency, fairness, democratic governance, efficiency, responsiveness, responsibility, and integrity which is based on citizens’ perception of government revenues and expected corresponding benefits. Therefore, this study explored how tax accountability affects tax administration effectiveness in southwestern states, Nigeria. The data were gathered from 9,600 respondents across all southwestern states, Nigeria which cut across eligible individual taxpayers and internal revenue service staff and analysed with Anova. The findings of the study showed that accountability and public trust have significant effect on tax administration in southwestern states, Nigeria. Also, it was discovered that transparency and trust also provided positive significant effect on effectiveness of tax administration. Furthermore, political accountability was found having positive influence on tax administration in southwestern states, Nigeria. Lastly, legal accountability was also discovered having positive effect on tax administration effectiveness. Conclusively, tax accountability has positive significant effect on tax administration in southwestern states, Nigeria. Based on the conclusion, it is recommended that to improve on transparency, government should allocate more tax revenue towards building infrastructure and social projects which will honourably encourage and enhance tax payment fulfilment by the taxpayers. This study also suggests that a well-structured tax administration system is crucial for establishing a tax framework built on a solid foundation for the effectiveness of tax administration in southwestern states, Nigeria.